Toward the Establishment of Discernment Theory: A Phenomenological Study of Discernment in Strategic Leadership Decision Making - Hurlbut, Bryan G. (My University, 2014)
The purpose of this research is to study and learn the basis for discernment as a strategic leadership decision mechanism and whether it can be validated and mapped as a process due to the increased demand for spiritually minded leaders in the workforce (Ivancevich et al., 2011; Phipps, 2012; Yukl, 2010). Since discernment begins as a non-cognitive decision-making process, it requires structure and guidelines so that strategic leaders may feel secure in using or denying it. The scope of this research involves multiple levels of leaders from within the Four square denomination in the state of Kansas. The primary questions being addressed are how discernment is used in strategic leadership decisions; whether discernment is part of, expands or replaces purely cognitive decision-making; whether discernment can be attributed to intuition or vice versa; and, the dynamics that exist when group discernment experiences agree with or contradict the individual participants. The effect of this research is to help identify possible flaws in decision making among constituents who rely on discernment so such flaws may be observed and avoided, and to identify ways to capitalize on discernment in the strategic leadership decision making process. The results of this research yield multiple discernment observations, namely: a 13-step identifying process, diminishing factors, relational interests, self-awareness factors, the importance of backward looking, the involvement of anxiety aversion and observations on group dynamics.